Clinical manifestation of experimental water intoxication in calves - Maribei, J M; Njoroge, E M; Mbugua, P N (The Indian Journal of Animal Sciences, 2012)
Two trials of induction or water intoxication, at weaning and 1 month after weaning were carried out in 5 test and 5control calves. The test calves did not have any access to salts and water, other than that contained in milk. for the wholepreweaning period. The control calves had water ad lib. throughout the preweaning period. To induce water intoxicationin the test calves, water was provided ad lib. at weaning and calves allowed to drink voluntarily. After the initial diseaseepisode at weaning, water was provided to test calves at small amounts equivalent to the volume of milk provided beforeweaning and a second trial of disease induction carried out 1 month later. In both trials, varying degrees of clinical signsof the disease were observed in all the 5 calves while none of the signs were observed in control calves. The signsobserved included haemoglobinuria, CNS disturbance, colic, diarrhoea, arrhythmia, oedema of the cydids, blindnes,excessive lacrimation, and excessive salivation.